Multi-Parameter Fluorescence-Activated Cell Sorting and Analysis of Stem and Progenitor Cells in Myeloid Malignancies - Will, Britta (2010)
Owing to the discovery that rare leukemia-initiating cells (or leukemia stem cells, LSC) give origin to and propagate a hierarchical cellular organization of variably differentiated leukemic blasts, the analysis of precisely defined stem and progenitor cells has increasingly gained importance. Emergence of multi-parameter high-speed fluorescence-activated cell sorting (FACS) for the subfractionation of hematopoietic progenitor cells has allowed research on the biology of the cell-of-origin for LSCs and of LSCs as potential (or essential) therapeutic targets that may escape chemotherapy and consequently contribute to disease relapse. This review introduces the current state-of-the-art methods for the fractionation of hematopoietic stem and progenitor cells, with particular focus on myeloid malignancies. As many aspects of human normal and malignant hematopoiesis are frequently modeled in animal studies, we also provide an overview of hematopoietic stem and progenitor cell purification methods that are commonly utilized for research in murine models of disease.